2014
DOI: 10.1080/13602381.2014.931045
|View full text |Cite
|
Sign up to set email alerts
|

Governmental influences on the evolution of agricultural cooperatives in Vietnam: an institutional perspective with case studies

Abstract: Using an institutionalist approach as the main framework, this research examines the evolution of Vietnamese agricultural cooperatives over the last six decades through four distinct phases -the voluntary collectivization period of 1954-1975, the compulsory collectivization period of 1975-1981, the de-collectivization period of 1981-1997 and the neo-collectivization period since 1997. Based on two case studies, this research examines the role of the Vietnamese government in the development of Vietnamese agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…https://www.ecologyandsociety.org/vol25/iss1/art31/ regarding crops, diseases, seasonal calendars, and harvest techniques. In addition, the mechanical structure and operation of the agricultural cooperative system limited the flexibility and creativity of fishers and farmers (Cox andLe 2014, Raymond 2008). New livelihood practices also undermined the social cohesion among former fishers and eroded their fishing expertise.…”
Section: The Adaptive Cycle Of the Tam Giang Fishery Systemmentioning
confidence: 99%
“…https://www.ecologyandsociety.org/vol25/iss1/art31/ regarding crops, diseases, seasonal calendars, and harvest techniques. In addition, the mechanical structure and operation of the agricultural cooperative system limited the flexibility and creativity of fishers and farmers (Cox andLe 2014, Raymond 2008). New livelihood practices also undermined the social cohesion among former fishers and eroded their fishing expertise.…”
Section: The Adaptive Cycle Of the Tam Giang Fishery Systemmentioning
confidence: 99%
“…The final list was revised to accommodate eight more topics: Law, policy, and institution, Internationalization, Entrepreneurial education, Poverty reduction, Job creation, Network development, Entrepreneur's motivations, and values, Technology application and Issues in Vietnam as listed below. Creativity and Innovation 38 (Brundenius and Le, 2014;Kiura et al, 2014;Le et al, 2018a;Nam et al, 2017;Tuan, 2015a;Vuong and Napier, 2015;Vuong et al, 2013) 5 Gender 8 (Le et al, 2016;Nguyen et al, 2014a;Oosterhoff and Hoang, 2018;Poon et al, 2012;Smith et al, 2017) 6 Inter-generations Transfer 14 (Le et al, 2018a;Ngo et al, 2018;Thu Hien and Santarelli, 2012;Trong Tuan, 2017a;Tuan, 2015b) 7 Organizational management 59 (Carbonara et al, 2018;Cox and Le, 2014;Dung and Janssen, 2015;Le, 2015;Nguyen, 2015;O'Cass and Ngo, 2011;Suzuki et al, 2014;Tran et al, 2016;Vuong, 2016c;Vuong et al, 2016d) 8 Social responsibility and orientation 28 (Luu, 2017;Napier and Quan Hoang, 2011;Nguyen and Nordman, 2018;Quan and Huy, 2014;Thai and Chong, 2013;Thi Bich et al, 2012;Vuong, 2016b;Walder and Nguyen, 2008) 9 Law, policy, and institution 39 …”
Section: Search Strategy and Identification Of Studiesmentioning
confidence: 99%
“…Contradict to previous findings that bribery or 'speed money' can help firms reduce cost arising from the complex and unpredictable legal practices in a transitional context, several studies on corruption have revealed that corruption has had a negative impact on firms' productivity and their abiding by state regulations (Tran et al, 2016;Vu and Le, 2016;Vu et al, 2018). It is suggested that supporting policy and regulation are not enough without careful supervision to achieve targeted goals (Cox and Le, 2014). More attention should be given to better allocating national resources among state and non-state sectors, and to eradicating any discrimination or promoting production efficiency of both sectors (Nguyen and Mort, 2016;Thi Nhung et al, 2015).…”
Section: Law Regulation and Policymentioning
confidence: 99%
See 2 more Smart Citations